Issues in Women's Land Rights in Cameroon. - Fonjong, Lotsmart N. (Langaa RPCIG, 2012)
This book explores the customary, social, economic political and rights issues surrounding access, ownership and control over land from a gender perspective. It combines theory and practice from researchers, lawyers and judges, each with track records of working on women and rights concerns. The nexus between the reluctance to recognize and materialize womenís right to land, and the increasing feminization of poverty is undeniable. The problem assumes special acuity in an essentially agrarian context like Cameroon, where the problem is not so much the law as its manner of application. That thi.